XPS, FTIR, EDX, and XRD Analysis of Al2O3 Scales Grown on PM2000 Alloy - K. Djebaili; Z. Mekhalif; A. Boumaza; A. Djelloul (Journal of Spectroscopy)
This work is an original example to compare the results obtained after calcination of Al2O3 hydroxides and oxidation of alumino-formers alloys. FTIR and XPS signatures were obtained for various oxidation temperatures and compared with those known from the literature about calcination of Al2O3 precursors. The aim of this work is to evaluate the use of IR spectroscopy and XPS analysis to probe the structural varieties of Al2O3. For this objective, a study of the PM2000 oxidation at various temperatures was conducted by means of XRD, IR spectroscopy, XPS analysis, EDX analysis, and SEM observations. This allowed us to clearly differentiate the transition Al2O3 from the α-Al2O3 and, amongst the transition Al2O3, to differentiate the characteristic of the IR spectrum of γ-δ phases from that of the θ phase.